An econometric model of Canada under the fluctuating exchange rate - Officer, Lawrence H. (Cambridge : Harvard University Press, 1968)
This study is a revised and extended version of the author's dissertation. The chapters cover: Stochastic Equation; Identities and the Complete Model and Impact Multipliers.
A revision of the author's thesis, Harvard University.
Bibliographical footnotes.
rpm 20/02/2018
Loans
Keywords: Econometrics; Exchange rate; Canada